2011
DOI: 10.1007/s11274-011-0952-7
|View full text |Cite|
|
Sign up to set email alerts
|

Plant growth promoting activity of an auxin and siderophore producing isolate of Streptomyces under saline soil conditions

Abstract: A biocontrol Streptomyces isolate (C) was tested for its plant growth promoting qualities under saline conditions. Exposure to elevated osmotic strengths up to 300 mM NaCl increased dry weight and cfu/ml significantly. The isolate C produced indolyl-3-acetic acid (IAA) into the medium in the amount of 2.4 μg/ml. The amount of auxin increased after adding salt and reached to 4.7 μg/ml in 300 mM NaCl. Biosynthesis of siderophore was detectable and increased in presence of NaCl. Streptomyces isolate C showed good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
154
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(174 citation statements)
references
References 33 publications
7
154
0
3
Order By: Relevance
“…The capability of auxin synthesis detected in many bacterial strains from the genera Azospirillium, Pseudomonas, Bacillus, etc., is thought to underlie the activation of plant root growth by these microorganisms [81]. Sadeghi et al demonstrated that a Streptomyces isolate increased plant growth in wheat and produced indole acetic acid and auxin in presence of salt [85]. Phytohormone-producing Bacillus sp.…”
Section: Production Of Plant Hormones and Other Beneficial Plant Metamentioning
confidence: 99%
“…The capability of auxin synthesis detected in many bacterial strains from the genera Azospirillium, Pseudomonas, Bacillus, etc., is thought to underlie the activation of plant root growth by these microorganisms [81]. Sadeghi et al demonstrated that a Streptomyces isolate increased plant growth in wheat and produced indole acetic acid and auxin in presence of salt [85]. Phytohormone-producing Bacillus sp.…”
Section: Production Of Plant Hormones and Other Beneficial Plant Metamentioning
confidence: 99%
“…The ability of Streptomyces to tolerate abiotic stresses including salinity, pH, and temperature and antibiotics and fungicide tolerance are widely reported (Waksman 1959, Gopalakrishnan et al 2012aSadeghi et al 2012). Consequently, it can be stated that these strains have the capability to survive in harsh environments and can be used in the integrated disease management programs.…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces are a group of Gram-positive bacteria, with high G + C content belonging to the order Actinomycetales, which form branched mycelia and hence sometimes been classified as fungi imperfecti. Plant growth promotion potential of Streptomyces was reported on bean (Nassar et al 2003), tomato (El-Tarabily 2008), pea (Tokala et al 2002), wheat (Sadeghi et al 2012) and rice (Gopalakrishnan et al 2012a, b). Streptomyces promote plant growth either by producing indole-3-acetic acid (Aldesuquy et al 1998) or siderophores (Tokala et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the rhizo sphere soils, root exudates are the natural source of tryptophan for rhizosphere microorganisms, which may enhance auxin (IAA) biosynthesis in the rhizos phere. Likewise Sadeghi et al (2012) have also reported the production of IAA and siderophore by halotolerant Streptomycetes isolate. Siderophore production may be involved in the inhibition of pathogens and thus pro mote plant growth indirectly because Streptomyces species are known for the production of hydroxamate type siderophores, which inhibit phytopathogen growth by competing for iron in rhizosphere soils (Khamna et al, 2009; Kaur et al, 2013), thus our isolates could be involved in the inhibition of pathogens.…”
mentioning
confidence: 86%
“…Kavya et al (2012), also reported salinity tolerance of Streptomycetes from Coringa man grove ecosystem but their results indicated a tolerance of 3-4% NaCl concentration, which is less as compared to isolates under current study. Sadeghi et al (2012) have reported the beneficial role of Streptomyces on PGP activity under salinity stress. Hence, it can be con cluded that these strains may have the ability to survive in the harsh environments such as saline and acidic to alkaline pH soils.…”
mentioning
confidence: 99%